Research on the Design of Micro-class Teaching Mode for Embedded Oral English Teaching in Senior High School - Liu, Meng (Journal of Theory and Practice of Contemporary Education, 2023)
This paper explores how to use the embedded method to carry out low-level oral makeup teaching in the listening and speaking class for 5-8 minutes. The design of the micro-class teaching mode of embedded oral makeup teaching, which is a class in class, is studied and discussed from the aspects of teaching principles, design principles, class structure, and class plan compilation. The New Curriculum Standards regarded the cultivation of students’ cultural awareness as one of the important teaching objectives. And in this globalized world, trades and exchanges between countries are increasingly common, so it is necessary to understand western cultures, which is the basis of cross-cultural communication ability. Language is the carrier of culture, and culture is the support of language, thus teachers should strength students’ cultural awareness through English reading teaching. This paper just takes a reading passage in “understanding ideas” part of unit 1 in NSE Book 1 for grade nine as an example, which aims to illustrate the practical teaching for developing students’ cultural awareness.